2010
DOI: 10.1073/pnas.1014348107
|View full text |Cite
|
Sign up to set email alerts
|

Domain structure of the DEMETER 5-methylcytosine DNA glycosylase

Abstract: DNA glycosylases initiate the base excision repair (BER) pathway by excising damaged, mismatched, or otherwise modified bases. Animals and plants independently evolved active BER-dependent DNA demethylation mechanisms important for epigenetic reprogramming. One such DNA demethylation mechanism is uniquely initiated in plants by DEMETER (DME)-class DNA glycosylases. Arabidopsis DME family glycosylases contain a conserved helixhairpin-helix domain present in both prokaryotic and eukaryotic DNA glycosylases as we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
105
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(110 citation statements)
references
References 39 publications
3
105
0
1
Order By: Relevance
“…Similar to the amino acid sequences in Arabidopsis, identified DNA methyltransferases (including MET1, DRM, CMT, and Dnmt2) and demethylases (including DME, ROS1, DML2, and DML3) from castor bean shared the conserved domains (Supplemental Figs. S1-S5), as reported previously in other plants (Finnegan and Dennis, 1993;Mok et al, 2010;Qian et al, 2014). Based on the structural features of these genes, in particular the presence and distribution of domains and motifs (Supplemental Fig.…”
Section: Identification and Characterization Of Dna Methylation-relatmentioning
confidence: 72%
“…Similar to the amino acid sequences in Arabidopsis, identified DNA methyltransferases (including MET1, DRM, CMT, and Dnmt2) and demethylases (including DME, ROS1, DML2, and DML3) from castor bean shared the conserved domains (Supplemental Figs. S1-S5), as reported previously in other plants (Finnegan and Dennis, 1993;Mok et al, 2010;Qian et al, 2014). Based on the structural features of these genes, in particular the presence and distribution of domains and motifs (Supplemental Fig.…”
Section: Identification and Characterization Of Dna Methylation-relatmentioning
confidence: 72%
“…GBD contains a Cys 6 -zinc cluster motif 26 and, as other zinc-coordinating DNA-binding proteins is expected to bind non-specifically to DNA while searching for its target site among an enormous amount of non-specific sites. 27 Furthermore, it has been reported that GBD is able to recognizes a variety of UAS sequences that adjust to the general formula (A/C)GGN [10][11][12] CCG and that DNA binding specificity is more stringent in vivo than in vitro. 28 We have shown that transient expression of GBD-ROS1_CD in HEK293 cells significantly increases transcription of a methylated 5xUAS-TK-Luc reporter gene.…”
Section: Discussionmentioning
confidence: 99%
“…Convincing biochemical and genetic evidence indicates that proteins belonging to a plant-specific family of DNA glycosylases directly excise 5mC from DNA and initiate active DNA demethylation through a base excision repair (BER) pathway. [7][8][9] Arabidopsis thaliana REPRESSOR OF SILENCING 1 (ROS1) is a representative member of this 5mC DNA glycosylase family, whose members are uniquely characterized by a discontinuous DNA glycosylase domain, 10 a conserved C-terminal domain that is essential for the catalytic activity, 11,12 and a basic amino-terminal domain that mediates nonspecific binding to DNA but it is not required for catalysis. 13 The understanding of active DNA demethylation mechanisms may have broad implications for epigenetic editing, a new discipline aimed to develop molecular tools to modulate gene expression.…”
Section: Introductionmentioning
confidence: 99%
“…DME 유전자는 비교적 큰 단백질을 코드하지만, C-말단 측 에 염기 제거복구에 관련된 DNA glycosylase와 비슷한 domain 구조를 가지고 있다 (Mok et al 2010). 애기장대에서 이와 상 동성이 높은 DME 유전자, DML2 유전자, DML3 유전자, ROS1 유전자 등 4개를 분리하였다고 하였다 (Zhu et al 2009).…”
Section: 자성 배우체의 모친 유래 후성유전학적 제어unclassified